2017
DOI: 10.3389/fimmu.2017.01291
|View full text |Cite
|
Sign up to set email alerts
|

LFA-1 Mediates Cytotoxicity and Tissue Migration of Specific CD8+ T Cells after Heterologous Prime-Boost Vaccination against Trypanosoma cruzi Infection

Abstract: Integrins mediate the lymphocyte migration into an infected tissue, and these cells are essential for controlling the multiplication of many intracellular parasites such as Trypanosoma cruzi, the causative agent of Chagas disease. Here, we explore LFA-1 and VLA-4 roles in the migration of specific CD8+ T cells generated by heterologous prime-boost immunization during experimental infection with T. cruzi. To this end, vaccinated mice were treated with monoclonal anti-LFA-1 and/or anti-VLA-4 to block these molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 47 publications
0
11
0
1
Order By: Relevance
“…In the spleen of chronically infected mice, CCL3 deficiency partially impaired CD8 + T-cells effector function, reducing IFNγ production after stimulus with the ASP2 T. cruzi antigen, in compatibility with the reduced frequency of IFNγ + CD8 + T-cells. However, the ASP2-specific cytotoxic activity was increased ccl3 −/− mice, paralleling the accumulation of CD8 + T-cells in spleen, and may contribute to systemic parasite control in the chronic infection, as cytotoxic CD8 + T-cells are crucial for parasite control (6,43).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the spleen of chronically infected mice, CCL3 deficiency partially impaired CD8 + T-cells effector function, reducing IFNγ production after stimulus with the ASP2 T. cruzi antigen, in compatibility with the reduced frequency of IFNγ + CD8 + T-cells. However, the ASP2-specific cytotoxic activity was increased ccl3 −/− mice, paralleling the accumulation of CD8 + T-cells in spleen, and may contribute to systemic parasite control in the chronic infection, as cytotoxic CD8 + T-cells are crucial for parasite control (6,43).…”
Section: Discussionmentioning
confidence: 98%
“…Reduced number of circulating leukocytes paralleled the accumulation of CD8 + T-cells in spleen of chronically infected ccl3 −/− mice. Moreover, the frequency of splenic CCR5 + LFA-1 + among CD8 + T-cells, a population that gain the blood, enter the heart tissue and play effector functions (6,15,43), was reduced in T. cruziinfected ccl3 −/− mice. These findings support that cell activation, trafficking and colonization of the heart tissue was disturbed in chronically infected CCL3-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in a recent study, Smith et al reported their work on variants controlling susceptibility to M. tuberculosis in the Collaborative Cross and that the Itgal gene is involved in the extreme susceptibility of CC042 mice to M. tuberculosis (46). Studies utilizing anti-LFA-1 antibodies to neutralize ITGAL protein activity have shown that ITGAL function is necessary for the timely clearance of respiratory syncytial virus (RSV) and for the control of parasitemia during Trypanosoma cruzi infection (36,47). In contrast, two separate studies have reported that Itgal Ϫ/Ϫ mice display increased resistance to Listeria monocytogenes infection (34,48).…”
Section: Discussionmentioning
confidence: 99%
“…This phenotype is likely partly explained by the Itgal deletion we have reported here. Studies utilizinganti-LFA-1 antibodies to neutralize ITGAL protein activity have shown that ITGAL function is necessary for timely clearance of respiratory syncytial virus (RSV) and for control of parasitemia during Trypanosoma cruzi infection [33, 43]. In contrast, two separate studies have reported that Itgal -/- mice display increased resistance to Listeria monocytogenes infection [31, 44].…”
Section: Discussionmentioning
confidence: 99%